Analysis of the usability of daily LiDAR measurements performed using Apple devices - Porzuc, Rafał; Kopniak, Piotr (Journal of Computer Sciences Institute, 2024)
The subject of this paper is the analysis of the usability of daily measurements performed by Apple devices equipped with LiDAR sensors. The study focuses on conducting research and analyzing the obtained results in terms of aspects such as accuracy, measurement sensitivity to disturbances, as well as the ability to perform measurements in various, sometimes challenging, situations. The outcome of the conducted research is to determine to what extent daily life can rely on measurements performed using Apple devices, what measurement errors need to be prepared for, but also in what situations these devices can help and replace conventional measuring tools.